Delayed closure of macular hole secondary to Terson syndrome after vitrectomy: A case report and literature review. Issue 31 (August 2019) - Sheng, Yan; Sun, Wen; Shen, Ye
Abstract: Rationale: Macular hole (MH) is a rare complication of Terson syndrome. Delayed closure of persistent MH after pars plana vitrectomy (PPV) is occasionally reported in literature, none of them is MH secondary to Terson syndrome. We describe a case of MH secondary to Terson syndrome and delayed closure occurred after PPV, and we also study the characteristics of delayed closure of persistent MH by reviewing related literatures. Patient concerns: A 61-year-old man presented with vitreous hemorrhage in right eye following a subarachnoid hemorrhage due to spontaneous rupture of his right vertebral artery dissecting aneurysm. The visual acuity was hand motion in the right eye and 20/30 in the left eye. Fundus examination showed dense and diffuse vitreous hemorrhage in the right eye. Diagnoses: Terson syndrome was diagnosed according to his subarachnoid hemorrhage history and vitreous hemorrhages in right eye. Interventions: PPV combined with phacoemulsification and intraocular lens implantation was performed in his right eye, and internal limiting membrane (ILM) peeling was also performed due to a MH noted during the surgery. Outcomes: One week after PPV, optical coherence tomography (OCT) showed a persistent MH. Without any intervention, the MH became smaller and flattened, with the best corrected visual acuity (BCVA) improved to 30/200 at 1 month after surgery. Six months later, the MH completely closed with BCVA improved to 20/40. According to our literature review, there are 8 cases of the delayed MH closure, which includes idiopathic MH (4 eyes), traumatic MH (2 eyes), and vitreomacular traction (2 eyes). There is no report about delayed closure of MH secondary to Terson syndrome. The times for these delayed closure occurred following PPV were ranged from 1 to 28 months. Holes even with obviously raised edges after PPV may spontaneously close, just like the case presented here. Lessons: Delayed closure of persistent MH after PPV is rarely reported. The significance of this case is to suggest that similar patients should be monitored carefully by OCT, and additional surgery for the MH may be delayed, since delayed closure is possible. The exact mechanisms of delayed closure of persistent MH still need to be clarified.